Tectonic subsidence at a fault intersection and its control on sediment accumulation in the Bohai Sea, eastern China - Wenqin Jiang; Weiguo Hou; Hongxian Chu; Yuekai Hao; Wang Song; Meiling Yin; Qingtong Wang (Marine Geology, 2026)

Salt-induced amino acid metabolism enhances nutritional quality of alfalfa: evidence from metabolomic profiling - Liying Liu; Meiling Hou; Yinghao Liu; Duowen Sa; Qiang Lu; Boyi Qi (Plant and Soil, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

CO2 selective adsorption from CO2/CH4 mixtures and regeneration of X zeolites by Li and K modification using various regeneration strategies - Yongbiao Sun; Hui Li; Haijun Lai; Yan Yu; Meiling Hou; Chao Fu; Zaizhou Wang; Chunxiang Zhang (Chemical Engineering Journal, 2025)

Characteristics and mechanisms of sea (salt) water intrusion in Laizhou City, Shandong Province, China - Linghao Kong; Hongxian Chu; Guohua Hou; Jiao Zeng; Liyuan Zhao; Xiangcai Han; Yachao Li; Faqiao Zhou; Meiling Yin; Xuzhen Zhang (Frontiers in Marine Science, 2025)
Sea (salt) water intrusion is a significant and ongoing geological disaster, and in recent years, it has become a notable concern for Laizhou City, Shandong Province. To identify the characteristics and mechanism of sea (salt) water intrusion in Laizhou City, samples of different types of water bodies (such as seawater, freshwater, slightly brackish water, brackish water, saline water, and brine) were systematically collected from the coastal zone area. The hydrochemical composition and evolution characteristics of the water bodies and the current situation, trends, and causes of sea (salt) water intrusion were analyzed. In 2020, the sea (salt) water intrusion reached 645.76 km 2 (including 151.64 km 2 of serious intrusion area), which is the largest ever recorded. The sea (salt) water intrusion had a strip-sheet distribution. From land to sea, groundwater gradually transitioned from the HCO 3 ·SO 4 ·Cl-Ca type to SO 4 ·Cl-Na·Ca and SO 4 ·Cl-Na types and then evolved to the Cl-Na type. Furthermore, from land to sea, the dominant cations and anions shifted from Ca 2+ and HCO 3 - to Na + and Cl - . The influence of seawater or brine gradually increased, that of Ca 2+ and HCO 3 - gradually decreased; whereas that of Cl - and Na + gradually increased, showing a division zone of freshwater → slightly brackish water → brackish water → saline water → seawater (brine) in the macroscopic territory. The freshwater, slightly brackish water, and brackish water bodies in the study area were controlled by evaporation and concentration processes and rock weathering leaching, whereas the saline water and brine were primarily controlled by evaporation and concentration processes. Groundwater salinity in the study area mainly originates from sea (salt) water intrusion, and locally groundwater salinity mainly originates from mineral dissolution or human activities. In addition, significant cation exchange adsorption occurred in slightly brackish and brackish water. Overall, these results will help to prevent and control seawater intrusions and improve disaster management.

Oxygen-containing functional groups of biochars enhancing the oxygen release of CaO2 and the generation of free radicals - Qiang Hu; Junheng Zhang; Yadi Pan; Kuan Ding; Chaoyang Xu; Jinyu Hou; Wuxing Liu; Chanchana Thanachayanont; Thipjak Na Lampang; Meiling Chen; Shu Zhang (Process Safety and Environmental Protection, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

Saikosaponins alleviate depression-like behaviors of chronic unpredictable mild stress exposed mice through ERK signaling pathway - Min Chen; Min Li; Liwei Ma; Huiling Hou; Meiling Tang; Qiang Li (Experimental Brain Research, 2025)

Nitric Oxide Promotes Adventitious Rooting in Cucumber Under Drought Stress Through Regulating Ascorbate Glutathione Cycle and Protein S-Nitrosylation - Xuemei Hou; Yuanyuan Dan; Nana Qi; Meiling Zhang; Changxia Li; Yihua Li; Yandong Yao; Weibiao Liao (Journal of Plant Growth Regulation, 2024)

Sheep dung deposition disrupted the soil microbiome in degraded grassland but not in non-degraded grassland - Yinghao Liu; Liying Liu; Meiling Hou (Environmental Research, 2024)

MnO2 nanozyme with lanthanide-based radiosensitization for advanced radiotherapy by tumor microenvironment triggering STING pathway activation - Meiling Tan; Zhimin Gao; Xiaozhao Wang; Chen Lin; Yuchi Wan; Wenyu Xie; Wei Chen; Yaru Zhang; Zewei Quan; Zhiyao Hou (Chemical Engineering Journal, 2024)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

The infertile individual analysis based on whole-exome sequencing in chinese multi-ethnic groups - Qiongzhen Zhao; Yanqi Li; Qi Liang; Jie Zhao; Kai Kang; Meiling Hou; Xin Zhang; Renqian Du; Lingyin Kong; Bo Liang; Weidong Huang (Genes & Genomics, 2023)

Self-intercepting interference of hydrogen-bond induced flexible hybrid film to facilitate lithium extraction - Meiling Wang; Tianyuan Zhang; Zhixiang Meng; Chongji Wang; Weikang Dong; Jijian Liu; Su Yang; Xudong Hou; Xiaoran Cheng; Weifeng Liu; Chenyang Xing; Xuguang Liu; et al. (Chemical Engineering Journal, 2023)

Comprehensive transcriptome analysis unravels the crucial genes during adventitious root development induced by carbon monoxide in Cucumis sativus L. - Fahong Yun; Dengjing Huang; Meiling Zhang; Chunlei Wang; Yuzheng Deng; Rong Gao; Xuemei Hou; Zesheng Liu; Weibiao Liao (Molecular Biology Reports, 2022)

Autonomous selfing is altered by pollination in delayed-selfing species Gentianopsis paludosa (Gentianaceae) - Qinzheng Hou; Xiang Zhao; Meiling Duan; Yiping Zhang (Brazilian Journal of Botany, 2022)

Genetic Structure and Diversity of Glycyrrhiza Populations Based on Transcriptome SSR Markers - Yaling Liu; Yaping Geng; Meiling Song; Pengfei Zhang; Junling Hou; Wenquan Wang (Plant Molecular Biology Reporter, 2019)

Genome-wide survey and expression analysis of the calcium-dependent protein kinase gene family in cassava - Wei Hu; Xiaowan Hou; Zhiqiang Xia; Yan Yan; Yunxie Wei; Lianzhe Wang; Meiling Zou; Cheng Lu; Wenquan Wang; Ming Peng (Molecular Genetics and Genomics, 2016)